Depressive symptoms increase fall risk in older people, independent of antidepressant use, and reduced executive and physical functioning. Issue 1 (January 2015) - Kvelde, Tasha; Lord, Stephen R.; Close, Jacqueline C.T.; Reppermund, Simone; Kochan, Nicole A.; Sachdev, Perminder; Brodaty, Henry; Delbaere, Kim
Highlights Depressive symptoms are associated with greater fall risk in older people. Depressive symptoms increase fall risk independent of antidepressant use. Depressive symptoms increase fall risk independent of reduced executive and physical functioning. Fall risk cumulatively increases with multiple impairments.